2011
DOI: 10.1186/1741-7015-9-25
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of vascular tone by adipocytes

Abstract: Recent studies have shown that adipose tissue is an active endocrine and paracrine organ secreting several mediators called adipokines. Adipokines include hormones, inflammatory cytokines and other proteins. In obesity, adipose tissue becomes dysfunctional, resulting in an overproduction of proinflammatory adipokines and a lower production of anti-inflammatory adipokines. The pathological accumulation of dysfunctional adipose tissue that characterizes obesity is a major risk factor for many other diseases, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 144 publications
(212 reference statements)
3
84
0
8
Order By: Relevance
“…Moreover, this group observed that leptin levels were positively correlated with TG, lipoprotein (a) [Lp (a)], Apo-A1, glucose, systolic blood pressure and diastolic blood pressure levels, and negatively with HDL-C levels in DM2 patients. Also, it has been proposed that the increased levels of leptin observed in obesity deregulates blood pressure control and results in hypertension, suggesting that leptin may also be a potential promoter of hypertension [38].…”
Section: The Role Of Leptin In Metabolic Syndrome and Diabetesmentioning
confidence: 99%
“…Moreover, this group observed that leptin levels were positively correlated with TG, lipoprotein (a) [Lp (a)], Apo-A1, glucose, systolic blood pressure and diastolic blood pressure levels, and negatively with HDL-C levels in DM2 patients. Also, it has been proposed that the increased levels of leptin observed in obesity deregulates blood pressure control and results in hypertension, suggesting that leptin may also be a potential promoter of hypertension [38].…”
Section: The Role Of Leptin In Metabolic Syndrome and Diabetesmentioning
confidence: 99%
“…Specifically, adiponectin reduces hepatic gluconeogenesis, increases glucose uptake by muscle and adipocytes, and reduces liver and muscle triacylglyceride accumulation while increasing fatty acid oxidation in these tissues (6). Along with these insulin-sensitizing actions, adiponectin exhibits cardioprotective and anti-inflammatory properties by acting directly on cardiomyocites, vascular cells, and macrophages, which has been proposed to underlie its beneficial effects on cardiovascular disorders (7)(8)(9)(10). Recent studies demonstrated that adiponectin also promotes cell survival of pancreatic ␤-cells (11) and may also play a role in the development and progression of distinct malignancies associated with obesity and insulin resistance, including breast cancer and colon cancer (12,13).…”
mentioning
confidence: 99%
“…ROS are known to induce inflammatory cytokines and, conversely, the cytokines also increase the ROS generation, thereby potentially forming a vicious cycle. [8][9][10][11][12][13][14]16,[19][20][21] Furthermore, a recent study by Banday and Lokhandwala 22 indicates that ROS increase the expression of Ang II receptors. Interestingly, the suppression of ROS production during the Ang II infusion almost completely abolished the persistent changes in the cytokines, Rac-1 and TBARS, following the discontinuation of Ang II infusion (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14]16 However, how the upregulation of these proteins decays after the withdrawal of RAS activation has remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation